Meningkatkan Aktivitas dan Hasil Belajar pada Pembelajaran PKn Siswa Kelas XC Multimedia SMKN 1 Banjarmasin dengan Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match - Yanti, Rusdiana (Lambung Mangkurat University Indonesia, 2015)
The background of this research is that low result study student because of students inclination not interest with Civics lesson moreover the last lesson because the students low interest with this lesson and students more interest with vocational in the school, very often some students doing activity self when the teacher explains the lesson, the concentration rupture, tired, browsing FB, wathing film, bored, moreover speak with another friends. Besides it, also some students go to school just to fulfill their obligations as students. Students be lazy for learn because they donât realize the importance learning for supplies in the future. Interest and motivation to learn is so low it looks on during the learning process of students when the teacher explains the less appreciated, they tend to not pay attention. This makes the low activity of students in learning so that learning outcomes were low, and when the written exam answers that mimics many friends as well as opening a book.Â Â Â Â Â Â Â Â Â Â Â This research aims to improve the learning activities undertaken by teachers using a type of cooperative learning type make a match. Increase student activity Civics students in learning the material in the Indonesian political system, and improving haisl students learn civics class XC MM SMK 1 Banjarmasin by using models of cooperative learning model make a match on the material in the Indonesian political system. This research was conducted in two cycles. Each procedure has a cycle of planning, execution, and observation, and reflection. Instrument used was a teacher and student observation sheet, as well as a written test.Â Â Â Â Â Â Â The results research of learning with the use of cooperative learning model make a match on Civics subjects showed deficits improve learning activities and learning outcomes Civics are as follows: (1) the activity students increased from cycle 1 to cycle 2 is 80% to 95%, (2 ) the activity student increase from cycle 1 to cycle 2 is equal to 77% to 90%, (3) result mastery learning students increase from cycle 1 with a percentage of 73% to 86%.Keywords: Activity Teacher, activities students, learning outcomes Civics, Cooperative Learning types make a match